Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Re: If the sequence x1, x2, x3, …, xn, … is such that x1 = 3 [#permalink]

Show Tags

19 Sep 2009, 06:07

13

This post received KUDOS

3

This post was BOOKMARKED

If the sequence x1, x2, x3, …, xn, … is such that x1 = 3 and xn+1 = 2xn – 1 for n ≥ 1, then x20 – x19 = A. 2^19 B. 2^20 C. 2^21 D. 2^20 - 1 E. 2^21 - 1

Soln: the shorter way of doing this is to start from x1, x(1) = 3 Now since x(n+1) = 2x(n) - 1 x(2) = 5 x(3) = 9 x(4) = 17 we can see the pattern now tat x(n) = 2^n + 1 therefore x(20) = 2^20 + 1 x(19) = 2^19 + 1

Hi, Bunnel Your explanation has always been a sigh of high relief to me. Owing to my sluggish expertise, I couldn't figure out as to how you were able to determine that there is a pattern and that is this:

We have the sequence x_1, x_2, x_3, …, x_n,… x_1=3 and x_{n+1}=2x_n - 1 for n\geq1.

Could you please throw light on as to how we should make out the pattern/serious in such questions?

Hi, Bunnel Your explanation has always been a sigh of high relief to me. Owing to my sluggish expertise, I couldn't figure out as to how you were able to determine that there is a pattern and that is this:

We have the sequence x_1, x_2, x_3, …, x_n,… x_1=3 and x_{n+1}=2x_n - 1 for n\geq1.

Could you please throw light on as to how we should make out the pattern/serious in such questions?

Thank you so much.

Well, there is no some kind of general technique to recognize a pattern. The first thing you should do is just write down several terms and look for a pattern.
_________________

I also find it hard to spot patterns specially under time constraints. Sometimes, I write down a couple of items and try to see the difference between each member but it doesn't seem to work that well. If anyone has any suggestions/techniques/tips that could make pattern recognition easier I would be more than grateful

Re: If the sequence x1, x2, x3, …, xn, … is such that x1 = 3 [#permalink]

Show Tags

24 May 2014, 06:52

srivas wrote:

If the sequence x1, x2, x3, …, xn, … is such that x1 = 3 and xn+1 = 2xn – 1 for n ≥ 1, then x20 – x19 = A. 2^19 B. 2^20 C. 2^21 D. 2^20 - 1 E. 2^21 - 1

Soln: the shorter way of doing this is to start from x1, x(1) = 3 Now since x(n+1) = 2x(n) - 1 x(2) = 5 x(3) = 9 x(4) = 17 we can see the pattern now tat x(n) = 2^n + 1 therefore x(20) = 2^20 + 1 x(19) = 2^19 + 1

so x(20) - x(19) = 2^20 - 2^19 = 2^19(2-1) = 2^19

soln is A

SorryI dont get the last part: 2^20 - 2^19 = 2^(20-19)...which is 2^1?

If the sequence x1, x2, x3, …, xn, … is such that x1 = 3 and xn+1 = 2xn – 1 for n ≥ 1, then x20 – x19 = A. 2^19 B. 2^20 C. 2^21 D. 2^20 - 1 E. 2^21 - 1

Soln: the shorter way of doing this is to start from x1, x(1) = 3 Now since x(n+1) = 2x(n) - 1 x(2) = 5 x(3) = 9 x(4) = 17 we can see the pattern now tat x(n) = 2^n + 1 therefore x(20) = 2^20 + 1 x(19) = 2^19 + 1

so x(20) - x(19) = 2^20 - 2^19 = 2^19(2-1) = 2^19

soln is A

SorryI dont get the last part: 2^20 - 2^19 = 2^(20-19)...which is 2^1?

Version 8.1 of the WordPress for Android app is now available, with some great enhancements to publishing: background media uploading. Adding images to a post or page? Now...

Post today is short and sweet for my MBA batchmates! We survived Foundations term, and tomorrow's the start of our Term 1! I'm sharing my pre-MBA notes...

“Keep your head down, and work hard. Don’t attract any attention. You should be grateful to be here.” Why do we keep quiet? Being an immigrant is a constant...